$\dfrac{9^n \times 3^2 \times 3^n -27^n}{3^{3m} \times 2^3}$ $=$ $\dfrac{1}{27}$

$27^n$ is an exponential term and it is subtracted from the product of the exponential terms $9^n$, $3^2$ and $3^n$ and the entire subtraction is divided by the product of $3^{3m}$ and $2^3$. The quotient of them is equal to the $\dfrac{1}{27}$. The value of $m-n$ is required to find by simplifying the equation.

Convert the exponential terms in the numerator to make every term contains number $3$ as base of the exponential term. It can be done by using power rule of exponents.

$\implies \dfrac{{(3^2)}^n \times 3^2 \times 3^n -{(3^3)}^n}{3^{3m} \times 2^3}$ $=$ $\dfrac{1}{27}$

The second term is $3^{3n}$ in numerator. The same quantity can be obtained by combining exponential terms $3^{2n}$ and $3^n$.

$\implies \dfrac{3^{2n} \times 3^2 \times 3^n -3^{3n}}{3^{3m} \times 2^3}$ $=$ $\dfrac{1}{27}$

$\implies \dfrac{3^{2n} \times 3^n \times 3^2 -3^{3n}}{3^{3m} \times 2^3}$ $=$ $\dfrac{1}{27}$

Apply product rule of exponents to combine $3^{2n}$ and $3^n$ as a single exponential term $3^{3n}$.

$\implies \dfrac{3^{2n+n} \times 3^2 -3^{3n}}{3^{3m} \times 2^3}$ $=$ $\dfrac{1}{27}$

$\implies \dfrac{3^{3n} \times 3^2 -3^{3n}}{3^{3m} \times 2^3}$ $=$ $\dfrac{1}{27}$

The exponential term $3^{3n}$ is a common term in the expression of the numerator. So, take it common from both terms.

$\implies \dfrac{3^{3n}(3^2 -1)}{3^{3m} \times 2^3}$ $=$ $\dfrac{1}{27}$

$\implies \dfrac{3^{3n}(9 -1)}{3^{3m} \times 2^3}$ $=$ $\dfrac{1}{27}$

$\implies \dfrac{3^{3n}(8)}{3^{3m} \times 2^3}$ $=$ $\dfrac{1}{27}$

The number $8$ can be expressed as $2^3$ due to the same quantity in the denominator.

$\implies \dfrac{3^{3n} \times 2^3}{3^{3m} \times 2^3}$ $=$ $\dfrac{1}{27}$

Cancel the $2^3$ by the same once to simplify it further.

$\implies \require{cancel} \dfrac{3^{3n} \times \cancel{2^3}}{3^{3m} \times \cancel{2^3}}$ $=$ $\dfrac{1}{27}$

$\implies \dfrac{3^{3n}}{3^{3m}}$ $=$ $\dfrac{1}{27}$

The value of $m-n$ is required to find. So, move $3^{3n}$ to denominator to combine both terms.

$\implies \dfrac{1}{3^{3m} \times 3^{-3n}}$ $=$ $\dfrac{1}{27}$

Apply product law of exponents to combine them as a single exponential term.

$\implies \dfrac{1}{3^{3m-3n}}$ $=$ $\dfrac{1}{27}$

$\implies \dfrac{1}{3^{3m-3n}}$ $=$ $\dfrac{1}{3^3}$

Use cross multiplication method to simplify the equation further.

$\implies 3^{3m-3n} = 3^3$

$\implies 3m-3n = 3$

$\implies 3(m-n) = 3$

$\implies m-n = \dfrac{3}{3}$

$\therefore \,\,\,\,\,\, m-n = 1$

The value of $m-n$ is $1$ and it is the required solution for this problem in mathematics.

Latest Math Topics

Latest Math Problems

Email subscription

Math Doubts is a best place to learn mathematics and from basics to advanced scientific level for students, teachers and researchers.
Know more

Learn how to solve easy to difficult mathematics problems of all topics in various methods with step by step process and also maths questions for practising.